Practice of defining levels of progressive electricity consumption by mining companies with underground kinds of iron ore mining - Синчук, Игорь Олегович; Беридзе, Татьяна Михайловна; Яловая, Алёна Николаевна; Винник, Марина Анатольевна (Technology audit and production reserves, 2015)
The paper presents a number of differences of iron ore mines from other industries, analysis of the factors that affect the electricity and energy effectiveness of mining enterprises and, consequently, on the levels and modes of electricity consumption. During the investigations it is developed the modern methodology of actual programs to improve energy efficiency of extraction of iron ore, which makes it possible to identify cost-effective measures aimed at the implementation of the existing energy potential in the enterprise. The authors presented a technique for assessing the state of power consumption modes of mining companies and their modeling and forecasting technique for determining the levels of power consumption and algorithm of its interval prediction. The article provides an analysis of intra-annual dynamics, which is essential for forecasting and the development of operational activities for qualified energy management industry.